Protective ability and specificity of convalescent serum from calves with Haemophilus somnus pneumonia. - Gogolewski, R P (1987)
The ability of convalescent serum to passively protect calves against Haemophilus somnus-induced pneumonia was studied. Preimmune and convalescent serum were obtained from calves before or after recovery from experimental chronic H. somnus pneumonia. Passive protection was assessed in another group of calves by intrabronchial inoculation of H. somnus that had been incubated with preimmune or convalescent serum. Each calf was inoculated with each treatment in alternating caudal lung lobes. Twenty-four hours after inoculation almost no pneumonia was present in lungs inoculated with bacteria incubated with convalescent serum, whereas severe pneumonia was present in lungs inoculated with bacteria incubated with preimmune serum. Quantitation of calf pneumonia in both treatment groups indicated a significantly different protective capacity between convalescent serum and preimmune serum (P less than 0.0005). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by Western blotting of purified H. somnus lipopolysaccharide resulted in intense reactivity with convalescent serum, but no reactivity was detected with preimmune serum. After sodium dodecyl sulfate-polyacrylamide gel electrophoresis of H. somnus outer membrane-enriched fractions, Western blots with convalescent serum gave intense reactions against H. somnus outer membrane antigens with apparent molecular masses of 78 and 40 kilodaltons and weaker reactions with 60-, 34-, 31-, 29-, 18-, and 15-kilodalton outer membrane antigens. No reactivity was detected with preimmune serum. Antibodies eluted from H. somnus after adsorption of convalescent serum reacted almost identically to unadsorbed convalescent serum in Western blots against bacterial outer membrane-enriched fractions. Thus, most of the antigens recognized by convalescent serum are likely to be on the bacterial surface and accessible to antibody. Surface antigens recognized by protective convalescent serum are candidate antigens for a subunit vaccine against H. somnus pneumonia.